Experimental investigation on the performance of domestic refrigerator using isobutane and mixture of propane, butane and isobutene - Sattar, M.A.; Saidur, Rahman; Masjuki, Haji Hassan (AU Journal, 2008)
This paper presents an experimental investigation on the performance of a domestic refrigerator using pure isobutane and mixture of propane, butane and isobutene as a refrigerant. The experiment was conducted with a refrigerator designed to work with HFC-134a under the same no load condition at a surrounding temperature of 25°C and 28°C. The refrigeration capacity, the compressor power, the coefficient of performance (COP), condenser duty and heat rejection ratio were investigated. The compressor consumes 2.08kWh/day and 2.25kWh/day when R-134a was used as refrigerant at 25°C and 28°C ambient temperature but when isobutane was used it consumed 2.131kWh/day and 2.183kWh/day at same condition. Where as the compressor consumed 2.625kWh/day and 2.758kWh/day when mixture of 70 Propane, 25 Butane and 5 Iso-butane was used and 2.515kWh/day and 2.579kWh/day when mixture of 50 Propane, 40 Butane and 10 Iso-butane was used at 25°C and 28°C ambient temperatures respectively. It can be stated that the performance of iso-butane is comparable with the performance of the HFC134a. The result shows a better performance of iso-butane than HFC134a. The results support the possibility of using iso-butane as an alternative to HFC134a in domestic refrigerators without modification of the components.